The ingroup as pars pro toto: projection from the ingroup onto the inclusive category as a precursor to social discrimination - Wenzel, M.; Mummendey, A.; Weber, U.; Waldzus, S. (Personality and Social Psychology Bulletin, 2003)
In an approach to intergroup discrimination and tolerance, it is assumed that the outgroup's difference from the ingroup is evaluated with reference to the prototype of the higher-order category that includes both groups. Two correlational studies yielded evidence that (a) group members tend to perceive their ingroup as relatively prototypical for the inclusive category (projection), (b) members highly identified with both ingroup and inclusive category (dual identity) tend to project most, and (c) relative prototypicality is related to negative attitudes toward the outgroup. The latter relation was further specified in Study 3, manipulating the valence of the inclusive category. Projection was related to more negative attitudes toward the outgroup when the inclusive category was primed positively but to more positive attitudes when it was primed negatively. The meaning of dual identities for intergroup relations is discussed.